Radio and X-ray study of cygnus A - Steenbrugge, K; Blundell, K (2007)
We present a comparative analysis of 5 GHz VLA and 200 ks Chandra ACIS-I image. In the 5 GHz image the familiar jet and much weaker counterjet are seen, which bend as the jet propagates towards the hotspots. Furthermore, where the lobe detected in 5 GHz emission starts to interact with the jet, we see that the jet "threads". In the 0.2-10 keV X-ray image we do not detect the jet, but do detect a relic of the counterjet.